Forecasting the prison population - predicting the consequences of sentencing policy - Grove, Peter (OR insight, 1998)
This paper describes the development of a new methodology for making ‘long’ term projections of the Prison Population. The methodology is based on a flow model of offenders in and out of prison, allowing the effect of changes in court sentencing policy to be predicted. The heart of the methodology is a new theory of offending, allowing the number of first time offenders to be predicted and also the recidivism of those released from prison.